2019
DOI: 10.1126/sciadv.aay0370
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TNFR2 and IL-33 as therapeutic targets in localized fibrosis

Abstract: IL-33 mediates cross-talk between immune and stromal cells in localized fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…Furthermore, we show that collagen VI regulates expression of the chemokines CCL2, CCL7, and CCL26, in accordance with previous data suggesting a potential role of endotrophin (ETP) in chemotaxis (60), and we confirmed a role of collagen VI in myofibroblast-induced chemotaxis of THP1 cells. Previously (4), we identified macrophages and mast cells as the predominant source of TNF within Dupuytren's nodule cultures and demonstrated that macrophage-derived TNF plays a key role in promoting the fibrotic phenotype in Dupuytren's disease (4). Excessive production of collagen VI may contribute to the chronicity of the disease by promoting the recruitment of monocytic cells to the site of this disease and probably plays a similar role in other fibrotic disorders (61).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, we show that collagen VI regulates expression of the chemokines CCL2, CCL7, and CCL26, in accordance with previous data suggesting a potential role of endotrophin (ETP) in chemotaxis (60), and we confirmed a role of collagen VI in myofibroblast-induced chemotaxis of THP1 cells. Previously (4), we identified macrophages and mast cells as the predominant source of TNF within Dupuytren's nodule cultures and demonstrated that macrophage-derived TNF plays a key role in promoting the fibrotic phenotype in Dupuytren's disease (4). Excessive production of collagen VI may contribute to the chronicity of the disease by promoting the recruitment of monocytic cells to the site of this disease and probably plays a similar role in other fibrotic disorders (61).…”
Section: Discussionmentioning
confidence: 86%
“…Using the relatively early-stage nodules from patients with Dupuytren’s disease enables us to analyze signaling and regulatory pathways and hence has the potential for the identification of novel therapeutic targets. Dupuytren’s nodules represent a complex disease system, housing densely packed myofibroblasts (MFs) alongside other less abundant stromal and immune cells ( 4 ). Myofibroblasts are characterized by the expression of α-smooth muscle actin (α-SMA) and excessive production of extracellular matrix (ECM) proteins such as collagens, glycoproteins, and proteoglycans, which enhances their ability to contract tissue ( 5 , 6 ).…”
mentioning
confidence: 99%
“…Although the study primarily focused on the combined effects of TNF-α and IL-33, we believe it supports our findings. Izadi and colleagues did not record much spontaneous IL-13 release ( 11 ), which may be due to cells being latent following disaggregation from tissue; IL-33 is known to drive IL-13 release from mast cells in disease ( 43 ). The current study has demonstrated that IL-13 release and its downstream fibrotic effects are viable targets for therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that Krüppel-like factor 4 (KLF4), a zinc finger transcription factor, can ameliorate chronic kidney disease through mitigating TNF-mediated tissue injury and fibrosis [ 50 ]. Moreover, TNF- α can stimulate IL-33 secretion via interaction with TNFR2 and which promotes myofibroblast development to accelerate the process of myocardial fibrosis [ 51 ]. NOD-like receptor protein 3 (NLRP3) inflammasome inhibitor, MCC950, is first demonstrated to ameliorate nonalcoholic fatty liver disease (NAFLD) and fibrosis in obese diabetic mice, and the targeting of NLRP3 is a logical direction in pharmacotherapy for liver fibrosis [ 54 ].…”
Section: Molecular and Cellular Mechanisms Of Fibrosismentioning
confidence: 99%